Emyooga Programme and Job Creation in Kabale District Uganda. - Niwasasira, Saviour (Kabale University, 2024)
The study evaluated the factors that have hampered the performance of the Emyooga programme in terms of job creation in Kabale District. “Emyooga” is a Runyankore word meaning skills. The purpose of the study was to examine the effect of the Emyooga programme on job creation in Kabale District since the programme’s inception in 2019. The study was guided by specific objectives which included: assessing the extent to which the Emyooga programme has contributed to job creation in Kabale District; examining the relationship between governance structures in the Emyooga programme and job creation in Kabale District; establishing the relationship between the capacity-building mechanisms in the Emyooga programme and job creation in Kabale District; and, to evaluate the relationship between infrastructure framework in the Emyooga programme and job creation in Kabale District. The study was anchored on the“Theory of Change” whose roots are traced back to the 1990s. This study adopted cross-sectional and correlation research designs and employed both quantitative and qualitative approaches for data collection and analysis. Census and simple random sampling techniques were employed to select a sample of 176 from a study population of 268. Questionnaires, documentary reviews and interviews were used to collect primary data. The study covered 94.9% (167 ) of the targeted sample of 176. Quantitative data was analysed using descriptive and inferential statistics with SPSS Ver.14, while qualitative data was collected and organised into codes generated from the most common responses to enhance the interpretation of results. The study revealed that through the Emyooga programme, more jobs are being created, hence contributing to GDP growth in Kabale and Uganda at large. It further revealed that well-formulated governance structures facilitated the delivery of the programme objectives. Capacity-building mechanisms like training within the Emyooga programme to accommodate all levels of literacy among beneficiaries were critical and accounted for its level of success. In this regard, the study revealed the existence of infrastructure like offices, computers and software systems but these were not responsible for promoting job creation. The study concluded that the Emyooga programme has the potential to expedite the process of socioeconomic transformation, especially through groups of individuals sharing a common goal.